LEAN & HEALTHCARE ORGANIZATIONS - A SYSTEMATIC LITERATURE REVIEW WITH BIBLIOMETRIC ANALYSIS ON APPLICATION OF LEAN HEALTHCARE IN BRAZIL - Ferreira, William de Paula; da Silva, Adriano Maniçoba; Tanaka, Wilson Yoshio; Zampini, Eugênio de Felice (Brazilian Journal of Operations & Production Management, 2016)
Despite having its roots in the Japanese automotive industry, Lean philosophy has been successfully applied in many companies of different sectors. In recent years several studies have been done regarding the potential of this managerial technology that may transform the healthcare organizations. The objective of this theoretical research paper is to conduct a Systematic Literature Review (SLR) with bibliometric analysis on application of Lean healthcare in Brazil. The aim is to understand the advancement of this research field in Brazil, investigating how Lean thinking has been put into practice and how this innovation has helped those companies to deliver more value to its customers. Peer reviewed articles were searched in 9 data sources. At first, a total of 5,473 articles were identified, which were reduced to 2,983 after Endnote software duplicate reference analysis. 789 articles were screened, after reviewing the adherence to the topic. Resulting in a sample of only 9 articles, after all inclusion criteria were match. The results suggest that Lean thinking has been applied successfully in many healthcare organizations. However, the research field in Brazil is quite new, having a great potential to increase.